PENGARUH PENAMBAHAN INOKULUM CAMPURAN TERHADAP PERUBAHAN KIMIA DAN MIKROBIOLOGI SELAMA FERMENTASI COKLAT - Maria Erna Kustyawati; Sri Setyani (Jurnal Teknologi & Industri Hasil Pertanian, 2008)
The effects of the addition of mixed inoculums consisted of Saccharomyces cerevisiae, Lactobacillus lactis and Acetobacter aceti on the chemical and microbial changes during cacao fermentation were investigated. The fermentation conditions were designed as natural fermentation (without any inoculum addition), fermentation added with mixed inoculums at zero fermentation time, and fermentation added with S. cerevisiae, L. lactis, and A. aceti at the zero, first, and second day of fermentation, respectively. The fermentation was conducted in the sweat box of 5 kg for 5 days and sampling was done at every 12 hours. The result showed that the addition of mixed inoculums at zero time speeded the optimum fermentation time. Microbial inoculums added at the first or second day of fermentation are not recommended. Keywords: Cacao bean, chemical and microbial changes, fermentation, mixed inoculums